STRATEGI SASTRA CYBER PADA ARENA KESUSASTRAAN INDONESIA: PERSPEKTIF PIERRE BOURDIEU (CYBER LITERARY STRATEGY IN THE INDONESIAN LITERARY ARENA: PIERRE BOURDIEU’S PERSPECTIVE) - Anindita Fikri Amalia, Redyanto Noor (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
AbstractCyber Literary Strategy In The Indonesian Literary Arena: Pierre Bourdieu’s Perspective.Digital technology makes cyber literature also has a role in the development of Indonesianliterary repertoire. This study uses qualitative research methods to find (1) cyber literaturestrategies in the Indonesian literary arena and (2) the legitimacy of the cyber literary arenain the Indonesian literary by using arena theory in Bourdieu's perspective and libraryresearch methods. The results of this study is (1) capital reconvention strategies andreproduction strategies are used to spread cyber literature and win the battle in theIndonesian literary arena; (2) cyber literature gets legitimacy it can develop and compete inthe Indonesian literary arena.Key words: cyber literature, strategy, legitimacy, arena, bourdieuAbstrakStrategi Sastra Cyber Pada Arena Kesusastraan Indonesia: Perspektif Pierre Bourdieu.Perkembangan teknologi digital menjadikan sastra cyber pun memiliki peran dalamperkembangan khasanah kesusastraan Indonesia. Penelitian ini menggunakan metodepenelitian kualitatif dengan tujuan untuk menemukan (1) strategi sastra cyber dalam arenakesusastraan Indonesia dan (2) legitimasi arena sastra cyber dalam arena kesusastraanIndonesia dengan menggunakan teori arena dalam perspektif Bourdieu dan metode penelitiankepustakaan. Adapun hasil dari penelitian ini diketahui bahwa (1) strategi rekonvensi modaldan strategi reproduksi digunakan untuk menyebarkan sastra cyber dan memenangkanpertarungan dalam arena kesusastraan Indonesia; (2) sastra cyber mendapat legitimasi dariberbagai pihak sehingga dapat berkembang dan bersaing dalam arena kesusastraan Indonesia.Kata-kata kunci: sastra cyber, stategi, legitimasi, arena, bourdieu